A Literature Review of Health Workers Support to Increase Immunization Coverage Quality - Lantin Sulistyorini (Faculty of Nursing, Universitas Jember, 2018)
The contribution or support of health workers towards the strengthening of immunization services still needs to be improved. The potential of health workers to improve the strategy and coverage of immunization needs to be developed. The coverage of routine immunizations associated with health care systems, healthcare providers, and parent-related services remains a barrier to improving the quality of immunization coverage. The search strategy for English studies relevant to the topic is done using ScienceDirect, SagePub, Springer database is limited from 2005 to 2018. Keywords used are “health workers support”, “immunization coverage”, “vaccination”. Full text articles are reviewed to select studies that match the criteria. The inclusion criteria in this review are health workers including nurses, doctors, community health workers. The search yielded 17 articles that fit the inclusion criteria. Improving the quality of immunization coverage by increasing the support of health workers as a strategy in health services. Finding the determinants that can improve immunization coverage, know the level of community satisfaction, and ensure various health care strategies